2017
DOI: 10.24198/jmpp.v1i1.13566
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Upah Minimum di Kabupaten Bandung

Abstract: AbstrakPermasalahan upah minimum terjadi di berbagai negara berkembang, yaitu banyaknya pekerja yang dibayar tidak sesuai dengan ketentuan upah minimum. Fenomena tersebut mengindikasikan bahwa upah minimum mungkin tidak menjadi alat yang efektif untuk meningkatkan kesejahteraan dan sebagai instrument dalam distribusi pendapatan. Tulisan ini bertujuan untuk menganalisis efektivitas upah minimum di Kabupaten Bandung. Dalam tulisan ini akan dikaji apakah upah minimum efektif sebagai alat kebijakan untuk meningkat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Home-based workers deserve the attention from all parties: entrepreneurs, government (executive and legislative), and other social institutions. Regulations for home-based workers are based on improper conditions in terms of wages and social security (4). Without the support from all stakeholders, significant changes to the welfare of home-based workers are difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Home-based workers deserve the attention from all parties: entrepreneurs, government (executive and legislative), and other social institutions. Regulations for home-based workers are based on improper conditions in terms of wages and social security (4). Without the support from all stakeholders, significant changes to the welfare of home-based workers are difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of the existing research found that there is still absent of any refutation or explanation of weaknesses of the idea of collaborative governance because they only explain the lack of effectiveness of the collaborative process 2 . 1 For example the application of collaborative governance in the program of water supply in California (Judith E. Innes, et al, 2006); in water resources management policy in Mexico (Sergio Graf Montero, 2006); policy on improving people's welfare in Korea (Sunhyuk Kim, 2010); in the forest rescue program in North Quensland (George R. Sranko, 2011); in labor protection policy (Nidhi Vij, 2011); in a low carbon tourism program (Heather Zeppel, 2012); in a sustainable city achievement policy in Western Australia (Margaret Gollagher and Janette Hartz- Karp, 2013); in the development of health and education in West Java (Jatti Indriati, 2015); and collaboration in disaster management in Yogyakarta (Muchammad Zaenuri, 2016) 2 See, for example, the effectiveness of collaboration in establishing minimum wages in Bandung (Elisa Susanti, 2016), and the findings of the effectiveness of collaboration in the management of international migrant workers in Yogyakarta (Izzul Fatchu Reza, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini menunjukkan bahwa pendapatan usahatani gula semut sebesar Rp 407.583,52/bulan dan gula cetak sebesar Rp 124.983,55/bulan berbeda secara signifikan dengan nilai lebih kecil dari UMK Purworejo 2018 yaitu sebesar Rp 1.573.000,-. Upah minimum merupakan upah bulanan terrendah yang terdiri atas upah pokok dan tunjangan tetap(Susanti, 2017). Nilai signifikansi pendapatan petani gula semut dan gula cetak kurang dari nilai probabilitas α (0,05) sehingga H0 ditolak dan H1 diterima.…”
unclassified